Permasalahan Surety Bond Sebagai Jaminan pada Pengadaan Konstruksi Milik Pemerintah di Universitas Bengkulu - Nurhani Fithriah; Edytiawarman Edytiawarman; Slamet Muljono; Dimas Dwi Arso (Universitas Batanghari Jambi, 2022)
This research aims to identify and analyze the existence of a Surety Bond as a guarantee in the procurement of government-owned construction, to analyze cases that arise in a Surety Bond as a guarantee in a government-owned construction procurement application, and to identify and analyze the application of a Surety Bond as a guarantee in construction procurement. at Bengkulu University. The research method was tested empirically and sociologically, information was obtained by means of a literature review and field research using direct interviews with parties involved in taking action against the research object's problems. The research results show that the existence of the Surety Bond as a guarantee in the procurement of government-owned construction is an indemnity agreement, the surety acts as a guarantor and is equal to the principal debtor who has the obligation to pay off his debts to the obligee together. If the guarantor is the principal who for some reason is negligent or negligent in fulfilling the obligation to complete the work promised to the obligee, the surety will guarantee on behalf of the guarantor who pays compensation up to the maximum amount determined by surety. Surety Bond as a guarantee in the government's construction procurement application is related to the transfer of risk, where the risk will shift to a third party (Insurance Industry). If the principal is negligent in carrying out its obligations, the surety who wants to pay the damages to the oblige (project owner) matches what is stated in the suretyship. The time limit for payment of compensation is within 14 working days after the guarantor receives notification of non- compliance of PPK or ULP. The application of the Surety Bond application as a guarantee in the procurement of construction at the University of Bengkulu was tried with the branch insurance industry. The branch insurance industry did not provide the guarantee to the head office in Jakarta, so the Head Office in Jakarta refused to pay the claim.